Symbolic Landscapes - Backhaus, Gary.; Murungi, John.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2009)
Symbolic Landscapes presents a definitive collection of landscape/place studies that explores symbolic, cultural levels of geographical meanings. Essays written by philosophers, geographers, architects, social scientists, art historians, and literati, bring specific modes of expertise and perspectives to this transdisciplinary and interdisciplinary study of the symbolic level human existential spatiality. Placing emphasis on the pre-cognitive genesis of symbolic meaning, as well as embodied, experiential (lived) geography, the volume offers a fresh, quasi-phenomenological approach. The editors articulate the epistemological doctrine that perception and imagination form a continuum in which both are always implicated as complements. This approach makes a case for the interrelation of the geography of perception and the geography of imagination, which means that human/cultural geography offers only an abstraction if indeed an aesthetic geography is constituted merely as a sub-field. Human/cultural geography can only approach spatial reality through recognizing the intimate interrelative dialectic between the imaginative and perceptual meanings of our landscapes/place-worlds. This volume reinvigorates the importance of the topic of symbolism in human/cultural geography, landscape studies, philosophy of place, architecture and planning, and will stand among the classics in the field.
Places Worlds -- I The Problematic of Grounding the Significance of Symbolic Landscapes -- The Road to Indian Wells: Symbolic Landscapes in the California Desert -- Wilderness as Axis Mundi: Spiritual Journeys on the Appalachian Trail -- Pu u Kohola: Spatial Genealogy of a Hawaiian Symbolic Landscape -- Mythological Landscape and Landscape of Myth: Circulating Visions of Pre-Christian Athos -- At Home on the Midway: Carnival Conventions and Yard Space in Gibsonton, Florida -- Crossing the Verge: Roadside Memorial Perth, Western Australia -- Life on The Avenue: An Allegory of the Street in Early Twenty-First-Century Suburban America -- Metaphor, Environmental Receptivity, and Architectural Design -- Geographical Sensibilities in the Arts -- II An Apology Concerning the Importance of the Geography of Imagination -- Semblance of Sovereignty: Cartographic Possession in Map Cartouches and Atlas Frontispieces of Early Modern Europe -- Symbolism and the Interaction of the Real and the Ideal: Scenery in Early-Modern Netherlandish Graphic Art -- Traversing One s Space: Photography and the féminine -- The Philadelphia Flower Show and Its Dangerous Sensibilities -- Gardening at a Japanese Garden -- Symbolic Space: Memory, Narrative, Writing -- Vienna s Musical Deathscape -- Crusoe s Island and the Human Estate: Defoe s Existential Geography.
Keywords: Philosophy; Aesthetics; Philosophy of nature; Geography; Regional planning; Urban planning; Philosophy; Philosophy, general; Philosophy of Nature; Aesthetics; Landscape/Regional and Urban Planning; Geography, general; Electronic books